(untitled) (Research, Society and Development, 2021)
In many countries, including Brazil and Spain, legislation and regulations have been implemented and improved with a focus on consolidating water planning and management instruments to achieve an integrated and sustainable management of water resources. Hydrological plans are included in this context as important means of promoting management in these premises. This paper analyses two basin plans, the Rio Doce, in southeaster Brazil, and the Miño-Sil, in northern Spain, in a case study approach. The analysis of official documents and legislation and the bibliographic research were used as data collection tools. As a result, the similarity between the two cases stands out in terms of the content of the plans, their objectives for environmental improvement in the basins they cover, the participatory approach in their preparation and the articulation of their processes and contents with international planning assumptions hydrological.